2018
DOI: 10.4103/ajns.ajns_67_18
|View full text |Cite
|
Sign up to set email alerts
|

Laminectomy versus laminoplasty in the surgical management of long-segment intradural spinal tumors: Any difference in neurological outcomes?

Abstract: Background:Previous comparative studies have shown that apart from lack of any significant difference in neurologic outcomes between laminoplasty and laminectomy following resection of intradural spinal tumours, spinal column issues such as postoperative deformities, malalignment, and adjacent level disease have also been clearly demonstrated to be quite similar for both techniques. However, there is no study yet that describes any difference in neurologic outcomes for long-segment intradural lesions as a rare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Technical advances in imaging, neuromonitoring, and minimally invasive approaches have been developed for surgery of intradural tumors, aiming to reduce complications and improve functional outcomes (8,9). The real clinical benefits of these new concepts for the treatment of extramedullary lesions remain a matter of debate in the literature (10)(11)(12)(13)(14). Intraoperative neurophysiological monitoring (IONM) could be considered a valid tool to detect in time, during the procedure, the occurrence of a neurological injury, then being able -potentially -to suggest both corrective measures to surgeons and to predict clinical outcomes in a short and long term follow-up (15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Technical advances in imaging, neuromonitoring, and minimally invasive approaches have been developed for surgery of intradural tumors, aiming to reduce complications and improve functional outcomes (8,9). The real clinical benefits of these new concepts for the treatment of extramedullary lesions remain a matter of debate in the literature (10)(11)(12)(13)(14). Intraoperative neurophysiological monitoring (IONM) could be considered a valid tool to detect in time, during the procedure, the occurrence of a neurological injury, then being able -potentially -to suggest both corrective measures to surgeons and to predict clinical outcomes in a short and long term follow-up (15).…”
Section: Introductionmentioning
confidence: 99%
“…While for degenerative disease or bone tumors in spine surgery the use of minimally invasive approaches showed to be effective and feasible in multiple examples (23)(24)(25) for IDEM tumors surgery evidence are few. The use of mono lateral laminectomy, indeed, and the use of technological tools such as the Cavitational Ultrasonic Surgical Aspiration (CUSA) should need for further investigations in order to add relevant data and report surgical experiences (13,26,27).…”
Section: Introductionmentioning
confidence: 99%
“…18,27 Another option is to perform a laminoplasty instead of laminectomy; however, the authors who compared both techniques have found no significant difference between both methods regarding the outcomes. 24 There were some limitations in our study, such as the small number of patients and the short duration of follow-up. We recommend a longer follow-up period to detect the actual rate of recurrence and late drawbacks of surgery such as spinal instability.…”
Section: Discussionmentioning
confidence: 92%
“…As reported by Onyia et al, retrospective evaluation in their study demonstrates that laminoplasty not to be more or less likely to have any better functional outcome or need for revision compared to laminectomy in the resection of longsegment intradural lesions. A quality randomized controlled study on a much larger scale will be required to validate this finding [12]. As it has been concluded by Ramesh et al [6] this type of flipped reposition laminoplasty is an excellent technique for the excision of IDEM tumours of the thoracolumbar spine and it provides adequate exposure of spinal canal as well as ad¬ditional stability to spine.…”
mentioning
confidence: 79%